The Effect of Ambon Banana Juice (Musa paradisiaca var. Sapientum Linn) and Sweet Starfruit Juice (Averrhoa carambola L) on Changes in Blood Pressure in the Elderly Men in the Community Health Center Work Area Tarus, Kupang Regency - Manek, Nusthen Aries; Datta, Frans Umbu; Refli, Refli; Lalel, Herianus J.D.; Manongga, Stefanus P. (Indonesian Journal of Medicine, 2023)
Background: Hypertension is a health problem that often occurs in society. Uncontrolled hypertension can trigger degenerative diseases such as heart disease and kidney failure. One of the therapies used to lower blood pressure is Ambon banana and sweet star fruit therapy. Subjects and Method: Research on elderly men suffering from hypertension in the Tarus Community Health Center working area used a Quasi-Experimental pretest–posttest with a Control Group research design. The number of samples in this study was 20 elderly men using a simple random sampling method. The dependent variable in this study was blood pressure, while the independent variable was the administration of Ambon banana juice, sweet star fruit juice, and a combination of Ambon banana juice and sweet star fruit juice. The measuring instrument used in this research is a questionnaire. The data analysis used in this research is Anova and Post hoc. Results: The average blood pressure in the elderly decreased after being given Ambon Banana Juice, Sweet Starfruit Juice, and a combination of Juices. The greatest reduction in blood pressure occurred in the group given Ambon banana juice (Mean= 140 mmHg; p=0.002), compared to sweet starfruit juice (Mean= 148 mmHg; p= 0.036), and these results were statistically significant. The juice combination also reduced the average blood pressure, but the results were not statistically significant (Mean= 156 mmHg; p= 0.454). Conclusion: The average blood pressure in the elderly decreased after being given Ambon Banana Juice, Sweet Starfruit Juice, and a combination of Juices. Keywords: hypertension, Ambon banana juice, sweet star fruit juice Correspondence: Nusthen Aries Manek. Universitas Negri Nusa Cendana Kupang. Jl. Adisucipto Penfui, Kupang, Nusa Tenggara Timur. Email: Nusthen2503@gmail.com. Mobile: 082144927619.